If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3a + 2a + -1(-2a) = -15 Remove parenthesis around (-2a) -3a + 2a + -1 * -2a = -15 Multiply -1 * -2 -3a + 2a + 2a = -15 Combine like terms: -3a + 2a = -1a -1a + 2a = -15 Combine like terms: -1a + 2a = 1a 1a = -15 Solving 1a = -15 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Divide each side by '1'. a = -15 Simplifying a = -15
| 3e-93=18e+60 | | (12-6x)=5(x+4)(6) | | x^2-6x-65=0 | | W(2+w)=48 | | f(x)=55x^2-122x-10 | | 33=3a | | Y-7=2(x-0) | | 1.5x+1=11 | | -12+20h+4h-2h=-10 | | 4(x+5)+5=21-x | | -2x-3y=15x+12 | | 2x-(3-3x)=12 | | (5x+10)(4x-10)= | | x+(12+x)=150 | | -5r-18r-(-16r)=14 | | secx/cosx-tanx/cotx=1 | | (6y-9)=-2y+13(3) | | 3y-14=22-y | | 8x-1=5x-22 | | 19.57=2s+4.61 | | 8v+11-3b=2b+2 | | (13s+7)(6s-18)=0 | | 3/4--1/2 | | 20y+y+4y-22y-2y=6 | | 15-3x=40 | | 6=m-(3+2m) | | 2(x+6)-5=16 | | -16x^2+66x+13=0 | | 13-3p=-8p-15-7 | | 2x^4-2x-1=0 | | (6x-7)-(8x+5)=0 | | 8x^2-43x-18=0 |